2011
DOI: 10.3233/jvr-2011-0573
|View full text |Cite
|
Sign up to set email alerts
|

Application of intergroup contact theory to the integrated workplace: Setting the stage for inclusion

Abstract: Social inclusion in community work settings remains an elusive outcome for many employees with intellectual disabilities. This study explored how the structure of work relationships with colleagues facilitates or inhibits social integration. Data were collected on 22 employees with disabilities through semi-structured interviews with six employment specialists and participant observations of six employees at their community worksites. Data were interpreted using intergroup contact theory, a longstanding theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Positive changes that follow intergroup contact have been observed with race relations (e.g., Emerson, Kimbro, & Yancey, ; Spanierman, Neville, Liao, Hammer, & Wang, ; Van Bavel & Cunningham, ), and pertinent to our work, with acceptance of individuals with intellectual disabilities (e.g., Burns, Storey, & Certo, ; Carter, Hughes, Copeland, & Breen, ; Findler & Vardi, ; Floyd, Purcell, Richardson, & Kupersmidt, ; Griffin, Summer, McMillan, Day, & Hodapp, ; Haring, Breen, Pitts‐Conway, Lee, & Gaylord‐Ross, ; Hughes et al., ; Kishi & Meyer, ; Krajewski & Flaherty, ; Novak, Feyes, & Christensen, ). Growing evidence suggests that acceptance of individuals with disabilities is facilitated when schools, social activities, and sports teams are “inclusive,” that is, when individuals with and without disabilities participate together as equals.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Positive changes that follow intergroup contact have been observed with race relations (e.g., Emerson, Kimbro, & Yancey, ; Spanierman, Neville, Liao, Hammer, & Wang, ; Van Bavel & Cunningham, ), and pertinent to our work, with acceptance of individuals with intellectual disabilities (e.g., Burns, Storey, & Certo, ; Carter, Hughes, Copeland, & Breen, ; Findler & Vardi, ; Floyd, Purcell, Richardson, & Kupersmidt, ; Griffin, Summer, McMillan, Day, & Hodapp, ; Haring, Breen, Pitts‐Conway, Lee, & Gaylord‐Ross, ; Hughes et al., ; Kishi & Meyer, ; Krajewski & Flaherty, ; Novak, Feyes, & Christensen, ). Growing evidence suggests that acceptance of individuals with disabilities is facilitated when schools, social activities, and sports teams are “inclusive,” that is, when individuals with and without disabilities participate together as equals.…”
mentioning
confidence: 58%
“…Additionally, 80% of college students who participated in Best Buddies (a program that fosters inclusive, reciprocal friendships) developed a more positive attitude about people with an intellectual disability and a better understanding of the challenges they face (Hardman & Clark, ). Across other studies, there is evidence that inclusive experiences can debunk myths and stereotypes (Bedini, ; Devine & Lashua, ; Devine & Wilhite, ; Novak et al., ) and foster friendships and social interactions (Bedini, ; Edwards & Smith, ; Kalyvas & Reid, ).…”
mentioning
confidence: 96%
“…As a result, it is possible that employers have already met, hired, and promoted people with disabilities without knowing it. Some studies suggest the use of disability awareness and sensitivity programs to educate all employees on how to reduce negative attitudes toward employees with disabilities (Martinez, 2013; Novak, Feyes, & Christensen, 2011). Collapsing the range of characteristics, capabilities and limitations of people with disabilities into a single category may perpetuate stereotypes and hinder the increased hiring and advancement of people with disabilities.…”
Section: Employer Perspectivesmentioning
confidence: 99%
“…Although contact theory has been applied to many situations, its connection to work contact has not been adequately explored. Existing research on workplace contact indicates a positive connection with reducing prejudice and stereotypes—given the right conditions (Donnelly & Hugas, ; Green, ; Lavie, ; Novak, Feyes, & Christensen, ). For example, Lavie () found that contact during work was associated with reduced antagonism but only when the status of workers from both groups are equal.…”
Section: Introductionmentioning
confidence: 99%